Guidelines for exploring interviews. How to ease need expression and disclosure of child abuse - Deza Villanueva, Sabina (2011)
This article makes some recommendations on how to raise the exploratory interviews with children who have experienced family violence and / or sexual abuse. Also it provides a set of guidelines to avoid victimization by operators of health care services. The text states that the overall objective of the interview with the boy or girl is getting to share their emotions, their needs and fears and to express the violence that has suffered. The topics covered are: Information prior to the interviewwith the girl or boy, Strategies to facilitate the expression of needs and emotions of the child, Strategies to start talking about the violence, Some guidelines for the exploratory interviews, return information collection and risk assessment.